O-2-Naphthyl diphenylthiophosphinate - Mague, Joel T.; Punji, Benudhar; Ganesamoorthy, Chelladurai; Balakrishna, Maravanji S. (Acta Crystallographica Section E-Crystallographic Communications, 2007)
The molecule of the title compound, C10H7OP(S)(C6H5)2 or C22H17OPS, exhibits distorted tetrahedral geometry about the P atom. The P=S bond of 1.9355 (4) Å is shorter than that found in Ph3P=S [1.950 (3) Å] because the replacement of one carbon on phosphorus by oxygen increases the effective electronegativity of the P atom, thereby enhancing pπ–dπ back-donation from a lone-pair orbital of the S atom.